Nonheme Iron‐Oxo‐Catalyzed Methane Formation from Methyl Thioethers: Scope, Mechanism, and Relevance for Natural Systems. Issue 43 (19th July 2017) - Benzing, Kathrin; Comba, Peter; Martin, Bodo; Pokrandt, Bianca; Keppler, Frank
Abstract: A range of nonheme oxo‐iron(IV) model systems with tetra‐ or pentadentate ligands is shown to produce methane from methionine and other thioethers. This model reaction for the natural aerobic production of methane is shown to proceed via two sulfoxidation steps involving the oxo‐iron(IV) complexes, with a bifurcation in the second step that either produces the sulfone or leads to demethylation with similar probabilities. In the presence of O2, the resulting methyl radicals produce methanol and formate or, in an O2 ‐depleted environment, lead to formation of methane. Abstract : Methionine and other methyl thioether natural products might be responsible for the formation of substantial amounts of the greenhouse gas methane.